If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = -9x + -2 + x(-3x + 6) Multiply f * x fx = -9x + -2 + x(-3x + 6) Reorder the terms: fx = -9x + -2 + x(6 + -3x) fx = -9x + -2 + (6 * x + -3x * x) fx = -9x + -2 + (6x + -3x2) Reorder the terms: fx = -2 + -9x + 6x + -3x2 Combine like terms: -9x + 6x = -3x fx = -2 + -3x + -3x2 Solving fx = -2 + -3x + -3x2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -2x-1 + -3 + -3x Simplifying f = -2x-1 + -3 + -3x Reorder the terms: f = -3 + -2x-1 + -3x
| 7u=-8u+30 | | 6+5(x-2y)= | | 15+6-4*28= | | 12-5*6= | | 5*23+7-62= | | 3*6-4= | | 3n-4=37 | | 54x-1=27x | | 12x^3+14x-48x=0 | | f(x)=In(x^3)(2x^4+1) | | 9+39+22/11-9+3 | | 2x-5(x-4)=-2+3x+4 | | 2x+9=7x-10 | | 5(n+2)=3/5 | | 1x^3+1x^2+c=0 | | (x-4)^(3/2)=16 | | y=4sinx+5 | | 1/2m=28 | | 9p^2+56=18p | | y=-x^2-5x+9 | | 3+2w=8-w | | 2a^2-6a-56=0 | | 2/3p+8=-4 | | 0=2x^2+2x-48 | | 2b-b=2b | | x+5/2=1-x | | a-b=b | | -4(5x+9)+4(x-7)= | | (x^2-4/(x-1)^2 | | 7.25-6m=46.25 | | r-21=37 | | w^2+4w-1=0 |